(3OYhGJ CejQ GdeDefjf jMji Hf MeRI hQSGFdgs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s ((3eMeO Hf jMji GdTheWi s)
(3ChdgG (B:s
(3GdMeO ddg hSdGe Ydi YHGOg GdPjf EUWai hHYO agPG cJGHfG jTJed ebUhOg Ydi YTQI aUhd s
(3BNQgG (B:s
(3hEPG de jcf GdaYd GdMSf efgG Edi GdeTGjN hdG Mhd hdG bhI EdG HGddg GdYdi GdYXje hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hUMHg hSde s
(3GdfSNI HgG MhGTs
(3cJHJ HYfGjI eGdcgG GdMSf Hf YHO Gddg GdCchYs
(3fSNI ebGHdI s
(3fSNI efbhdI ef fSNI cJHJ SfI (B994(3g` s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
Keywords: (3abg GdePGgH GdCNQis